Initial review of pregnancies in aberdeen related to H1N1 (SWINE FLU) 2009 influenza. (18th April 2012) - Haque, L; Fatima, F; Mathur, M
Abstract : Aim: To identify high risk patients and review management and outcome of swine flu affected pregnancies at Aberdeen Maternity Hospital. Methodology: A retrospective case note review of women admitted to hospital with confirmed or suspected H1N1v influenza infection in pregnancy from Oct 2009 to Nov 2009. Total number of patients identified was six. Data was entered and analysed using SPSS 16. Results: Among the affected women, 50% were between the age group of 16-25 years. 66% are primiparous or had one child. Average BMI was 30, Equal number of them were smoker and non-smoker. 67% had past medical problems such as asthma, Hypothyroid, depression. All had ITU admissions and average stay was 5 days. In relation to presenting symptoms all had tiredness/lethargy and 80% had cough, fever and 10% complained of breathlessness. There were 50% non immune (not vaccinated) women. All women were treated with Zanamivir and 2 patients had ECMO. Majority of them delivered at term and among these half had caesarean sections. Average birth weight was 2.9 kg. Conclusions: There should be a high index of clinical suspicion in pregnant women developing fever. There is good evidence of safety for both flu vaccines and antiviral medication and therefore pregnant women should be constantly reassured and advised to take flu vaccine.